2019
DOI: 10.1371/journal.pone.0212114
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus: Epidemiological surveillance of the Mexican Institute of Social Security

Abstract: IntroductionAt the end of 2015, the first cases of Zika were identified in southern Mexico. During 2016, Zika spread as an outbreak to a large part of the country's coastal zones.MethodologyThe Zika epidemiological surveillance system records cases with clinical symptoms of Zika virus disease (ZVD) and those confirmed by means of a reverse polymerase chain reaction (RT-PCR) assay. This report includes the suspected and confirmed cases from 2016. Incidence rates were estimated by region and in pregnant women ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…As for ZIKV, most symptoms were found in region 2 and region 4 ( Figure 2 ). Limited studies have shown region 5 to have many cases, but these studies have not examined the cases’ clinical symptoms as our research did [ 23 , 46 ]. The outcomes from the regional variation of symptoms may be used to look at the severity of symptoms comparing endemic vs. non-endemic municipalities to narrow down other regional differences, healthcare worker practices, and the possible role of access to publicly funded healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…As for ZIKV, most symptoms were found in region 2 and region 4 ( Figure 2 ). Limited studies have shown region 5 to have many cases, but these studies have not examined the cases’ clinical symptoms as our research did [ 23 , 46 ]. The outcomes from the regional variation of symptoms may be used to look at the severity of symptoms comparing endemic vs. non-endemic municipalities to narrow down other regional differences, healthcare worker practices, and the possible role of access to publicly funded healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV infection in humans remained a sporadic zoonotic disease in Africa and Southeast Asia until the first large urban outbreak that struck Micronesia in 2007 [ 1 ]. Over the next five years, the disease spread to Polynesia, Easter Island, the Cook Islands, and New Caledonia and was introduced and disseminated rapidly in South America in 2015 and to Central America and the Caribbean, including Mexico, the following year [ 2 , 3 , 4 ]. After these large epidemics, ZIKV infection has remained endemic with a low transmission rate in South and Central America, including Mexico, Peru, and Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that asymptomatic cases account for less than 30% [ 6 ] and not 80%, as previously estimated [ 7 ]. The characteristic clinical features include a fine maculopapular skin rash that is diffusely distributed and is associated with two or more of the following symptoms: fever, headache, nonpurulent conjunctivitis, arthralgia, pruritus, and retro-ocular pain [ 4 ]. However, the nonspecific clinical symptoms of ZIKV infection are often misdiagnosed as other arboviral infections, especially dengue virus (DENV) infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation of arbovirus cases: laboratory samples were not taken to confirm all DENV, ZIKV or CHIKV suspected cases; therefore, positive cases were estimated according to previous studies [36].…”
Section: Definitionsmentioning
confidence: 99%